Kepastian Hukum Terkait Hak-Hak Masyarakat Konservatif Dalam Pembangunan Ibu Kota Nusantara - Afifah, Dashilfa; Aristias, Adinda; Manullang, Imelda Arthameisia; Sukma, Nina Fitria; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of Ibu Kota Nusantara (IKN) as the new capital of Indonesia has significant impacts on various community groups, including conservative communities residing in the affected areas. Legal certainty is key to ensuring that their rights are protected during the development process. This study aims to analyze the potential violations of land rights and legal protection of environmental rights for conservative communities in the context of the development of Ibu Kota Nusantara, including rights to land, culture, livelihood, and socio-economics. This study analyzes various regulations and policies implemented to sustain the lives of conservative communities and evaluates the effectiveness of existing legal mechanisms in protecting their interests. The research method used is a normative juridical approach with an analysis of applicable laws and regulations as well as related literature reviews. The results show that there are no comprehensive policies regulating the recognition of indigenous communities in the Ibu Kota Nusantara area, leading to overlapping recognition between different regulations. Thus, there is a risk of violations of land and environmental rights for conservative communities due to the development policies of Ibu Kota Nusantara, which have not fully considered legal certainty for the interests and rights of the conservative communities living there.